The impact of the EU water framework directive on irrigated agriculture in England - Freeman, David (Cranfield University, 2005)
Irrigation in the England is a small but strategically important sector. It makes a significant contribution to agricultural GDP allowing the production of specialised crops with the ability to maintain and maximise both yield and quality. It is this demand for reliable, quality supplies of produce that drives the demand for irrigation water and is likely to increase in future. In some areas of East Anglia irrigation can account for up to 70% of water abstraction in the region during peak demand. Concerns over environmental quality combined with increasing pressures on scarce water resources have prompted the introduction of new regulation and tighter controls on resource distribution. The introduction of the Water Framework Directive (WFD) into European legislation aims to facilitate better water management and to improve quality of the water environment. Irrigation farming can lead to problems of water quantity and water quality as a result of abstraction and agrochemical discharges. This study aims to identify the mam irrigation farming systems in England; to determine the characteristics and performance of irrigation farming systems; to , evaluate the impacts of alternative policy measures on these systems and to determine possible coping strategies that could be adopted. Three case study farms have been used to develop a linear programming (LP) model to enable the assessment of alternative policy measures. ;Measures aimed at encouraging efficient use of water arid reduction in agrochemical discharges have been modelled in the LP and the· effect of these policy changes on the sustainability of farms investigated with respect to economic, social and environmental objectives. The study confirmed the links between irrigated agriculture, WFD and water resource and quality issues. The study indicated that the implementation of policy measure as a result of the WFD are likely to affect the sustainability of irrigated agriculture. The use of abstraction license restrictions and abstraction charge increases facilitated reductions in the use of water. Reduction in water/use availability led to reduced areas of irrigated cropping. Reductions in the areas of cropping are closely linked with the returns to water gained for each specific crop. Under water abstraction charge increases, reductions in water use were dependant upon the value of water to the crop, under high net margins the value of water was high and large areas of irrigated cropping remained in the system. This value could be up to £9.00m3 for strawberries and in the region of £1.00 -£2.00m3 for potatoes and vegetables. The inelastic nature of demand for irrigation water leads to a transfer of income from farmers to the regulatory body. General trends showed that the profits -to farms could be significantly reduced with the loss of irrigated crops. Labour requirements were also reduced significaantly with reductions in the areas of irrigated land. Environmental performance improved under reduced irrigation, confirming the high potential for pollution to occur under the irrigated crops with high levels of agrochemical inputs. Controls on the agrochemical losses impacted upon- the areas of land under production. The cropping pattern switched to the most profitable crops with the highest returns per unit of agrochemical loss. Irrigated crops became dominant within the cropping pattern. Areas of land were taken out of production in order to allow the maximisation of areas of irrigated cropping while allowing the farm unit to remain within the limits of agrochemical loss to the environment. Coping strategies were identified namely; the use of winter abstraction combined with a storage reservoir and the use of trickle irrigation as a more efficient method of application, their use was validated under licence restrictions and abstraction charge increases. Trickle irrigation and winter water strorage have been confirmed as being viable options in extending irrigation. The study identifies priorities for future research, including:- • Expansion of the examination of coping strategies, (this may include work on deficit irrigation), • Agrochemical use~ and possible yield and quality responses to reduced inputs, • Development of more complex models including the use of a greater range of cropping options and coping strategies, with the possibility of incorporating reduced input options and agri-environmental land use.